Equity of uptake of a diabetic retinopathy screening programme in a geographically and socio-economically diverse population - Orton, Elizabeth; Forbes-Haley, A.; Tunbridge, L.; Cohenc, S. (WB Saunders, 2013)
Objectives At the time of undertaking the audit, the uptake of diabetic retinopathy screening in Derbyshire was 73%, below the national standard of 80%. To assess equity of access to diabetic retinopathy screening in a geographically and ethnically diverse population and determine predictors for poor uptake that will inform service improvements.